Collaboration UMPSA, UMK, and MIGHT forge strategic alliance to advance Malaysia’s Rare Earth Industry - Naqiah, Puaad (UMPSA, 2025)
CYBERJAYA, 16 July 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Universiti Malaysia Kelantan (UMK), and the Malaysia Industry-Government Group for High Technology (MIGHT) have formalised a strategic partnership aimed at enhancing research, innovation, and commercialisation in the field of rare earth elements (REE).